(untitled) (Research, Society and Development, 2022)
The Problem-Based Learning (PBL) methodology is a teaching-learning method based on solving clinical, community or scientific problems. Currently, the PBL methodology is offered in Medicine and Dentistry courses at the University Center of Patos de Minas – UNIPAM. This study aims to evaluate the perception of professors of the Dentistry course at UNIPAM in relation to PBL. The sample consisted of professors of the Dentistry Course at UNIPAM, who used the Problem Based Learning – PBL methodology, and a questionnaire was applied to them. A descriptive statistical analysis of the epidemiographic data of the participants was carried out, as well as an analytical statistics of the data obtained. The questionnaires were applied in person to 14 professors. The average age of participants was 40.64 years. The comparative analysis of perceptions among professors of the course, according to the time of graduation in higher education, found that professors with less than 10 years of academic training more frequently perceived conflicts between students when compared to the group of professors with 10 or more years of formation. According to the academic title, professors with a PhD more frequently sought information about the methodology used in the course, both at the time of admission and before the moment of joining as professors in the UNIPAM Dentistry course. Regarding the time to fulfill the proposed objectives in a tutorial session, professors with a PhD considered that the time to fulfill the proposed objectives in a tutorial session is adequate.